Association of ANKRD55 Gene Polymorphism with HT: A Protective Factor for Disease Susceptibility - Yu-die Fang; Jing Zhao; Xin-juan Zhuang; Jian-bin Xu; Tian-tian Cai; Xiao-rong Yang; Kai-da Mu; Jin-an Zhang (International Journal of Endocrinology)
Purpose. Recent studies have shown that Ankyrin Repeat Domain 55 (ANKRD55) gene polymorphism is a risk factor for multiple autoimmune diseases, but its association with autoimmune thyroid diseases (AITDs) has not been reported. The purpose of this study was to investigate the potential relationship between polymorphism of the ANKRD55 gene and AITDs. Methods. For this study, we enrolled 2050 subjects, consisting of 1220 patients with AITD and 830 healthy subjects. Five loci (rs321776, rs191205, rs7731626, rs415407, and rs159572) of the ANKRD55 gene were genotyped using Multiplex PCR combined with high-throughput sequencing. Results. The results showed that the allele frequencies of rs7731626 and rs159572 loci in HT patients were lower than those in normal controls (P=0.048 and P=0.03, respectively). In different genetic model analyses, rs7731626 and rs159572 were also significantly correlated with HT in allele, dominant and additive models before and after age and sex adjustment. There were no differences in rs321776, rs191205, or rs415407 of the ANKRD55 gene in allele frequency or genotype frequency between AITDs patients and controls. Conclusions. This study for the first time found that rs7731626 and rs159572 of ANKRD55 were significantly correlated with HT, and individuals carrying the A allele at these two loci had a lower probability of developing HT.